Synonymy of Cryptopsocus Li with Trichadenotecnum Enderlein (Insecta: Psocodea: ’Psocoptera’: Psocidae) and description of three new species - Yoshizawa, Kazunori; Lienhard, Charles (Zootaxa, 2015)
The genus Cryptopsocus Li, 2002 is synonymized with Trichadenotecnum Enderlein, 1909. The type species of Crypto-psocus, T. cynostigmus (Li, 2002) n. comb., is considered to be a close relative of T. marginatum New & Thornton, 1976. These species cannot be assigned to any species group previously established in Trichadenotecnum so that the marginatum species group is here proposed for them. Three new species belonging to this species group are described: T. tigrinum and T. sharkeyi from Thailand and T. sabahense from Sabah, Malaysia. The phylogenetic position of the marginatum group is discussed using morphological data.